Numerical analysis of effective parameters in response of the nonlinear passive viscous systems - GholamReza Havaei (Journal of Structural and Construction Engineering, 2017)
In this article all the effective parameters in response of nonlinear passive viscous systems are investigated. Here, the term response is referred to the maximum inter-story drift and maximum absolute acceleration of the stories. Inter-story drift is known as the structural failure index and maximum absolute acceleration is known as the nonstructural and acceleration sensitive equipment in buildings. Based on the results, the more effective parameters in these systems are initial stiffness and strength of the building, amount of supplemental damping used in the system, stiffness of the braces connecting the dampers to the building and number of the stories. In order to show the effect of each pre-mentioned parameters, many linear and nonlinear passive control systems were analyzed by the time history method. For decreasing the influence of dominant input frequency of the excitation record and also for generalization, two white noise time histories normalized to the 1g were used as the input excitation. The results show that reduction of stiffness and strength are the key parameters in reducing absolute acceleration and also increasing the brace stiffness and supplemental damping are the most effective parameters in reduction of inter-story drift. In other words, if in design of passive control systems, only increasing the damping of the system is considered, the absolute acceleration of the system may be increased and as the result the acceleration sensitive equipment will experience the most failure during the earthquake.